2016
DOI: 10.1002/jcsm.12115
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of sarcopenia in patients with diffuse large B‐cell lymphoma treated with rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone

Abstract: BackgroundSarcopenia is known to be related to an increased risk of chemotherapy toxicity and to a poor prognosis in patients with malignancy. We assessed the prognostic role of sarcopenia in patients with diffuse large B‐cell lymphoma (DLBCL).MethodsIn total, 187 consecutive patients with DLBCL treated with induction rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone (R‐CHOP) immunochemotherapy were reviewed. Sarcopenia was defined as the lowest sex‐specific quartile of the skeletal muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
78
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 35 publications
(70 reference statements)
4
78
2
3
Order By: Relevance
“…With this in mind, our results contrast what is observed in other malignancies where low muscle mass alone was associated with worse overall survival and greater post‐operative morbidity . Most studies in other malignancies have found an impact of low muscle mass on overall survival, but only a few studies observed differences in progression‐free survival . In several malignancies, low muscle mass has been demonstrated to be strong predictor of both short‐ and long‐term outcomes .…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…With this in mind, our results contrast what is observed in other malignancies where low muscle mass alone was associated with worse overall survival and greater post‐operative morbidity . Most studies in other malignancies have found an impact of low muscle mass on overall survival, but only a few studies observed differences in progression‐free survival . In several malignancies, low muscle mass has been demonstrated to be strong predictor of both short‐ and long‐term outcomes .…”
Section: Discussioncontrasting
confidence: 94%
“…11,13,34,35 Most studies in other malignancies have found an impact of low muscle mass on overall survival, but only a few studies observed differences in progression-free survival. [36][37][38] In several malignancies, low muscle mass has been demonstrated to be strong predictor of both short-and long-term outcomes. 34,35,39,40 We may have identified differences in PFS had our patient cohort been more diverse in stage and presentation.…”
Section: Discussionmentioning
confidence: 99%
“…19 A gender-specific effect was also seen in a rat model of ageing with males being more prone to muscle loss, particularly when fed a high fat diet. 23 Sarcopenia is also associated with standard R-CHOP chemotherapy intolerance in patients with malignancies 24 and worse survival of patients with ovarian cancer receiving neoadjuvant chemotherapy. 25…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia, or the presence of low muscle mass, has been associated with decreased overall survival in patients with DLBCL [35]. However, the impact of sarcopenia on other outcomes, including treatment toxicity, treatment-related mortality, and ability to complete standard therapy, has not been well-studied in the DLBCL population.…”
Section: Introductionmentioning
confidence: 99%